Investigation of the free driving rotational body of the adaptor to the seeder of prosapic cultures - Прасолов, Є. Я.; Бєловол, С. А.; Черненко, Б. С.; Ужищенко, А. В.; Шеметюк, А. В. (Scientific Progress & Innovations, 2018)
The article presents the results of the development of a non-rotating rotational organ of the soil-working adapter to a seed drill of cultivating crops. The analysis of working bodies of soil-working machines was carried out; the constructive-technological scheme of the soil-working adapter is substantiated; defined angles of inclination and inclination of the disc body; comparative estimation of soil hardness indexes; defined rational parameters and operating modes of the working body; determined fractional composition of soil and loosening by the working body; researches have been conducted to determine the rational angle φ of the working organ; the longitudinal profile of the seed bed is established; the ratio of the width and depth of the treated strip is executed; the coefficients k1 and k2 in the formula of the traction resistance of the non-driven rotational body are determined. To improve the quality of pre-sowing soil cultivation, an adapter with a rotary rotary device to the seeders is proposed. It consists of a transverse beam of a frame, on which, with the help of brackets, there are sections of a non-rotating rotary body. To improve the quality of pre-sowing soil cultivation, an adapter with a rotary device to the seeders is offered. It consists of a transverse beam of a frame, on which, with the help of brackets, there are sections of a non-rotating rotary body. To copy the field profile, each section is provided with a parallelogram suspension and a spring-loaded rod. In addition to the transverse beam of the adapter frame consists of two auto-scraps, which serve for aggregating with the tractor, and auto-coupling with a drill, connected by a longitudinal beam. The testing of research results has been carried out, which confirms the efficiency and expediency for use in the farm of the PP agricultural firm «Anastasia» in Globyno district, Poltava region.